Konsep Implementasi Model dan Integrasi Pendidikan Karakter di Madrasah Ibtidaiyah - Abu Amar (IBTIDA', 2020)
In principle, the purpose of this paper is to determine the background of the application of character education and the concept of character education. By using a descriptive method of conceptual analysis of the notion of character education and the implementation of the character education model in Madrsah Ibtidaiyah. So far, the world of education in Indonesia is considered to have been less successful in bringing the nation's generation to be individuals with character and dignity. This is among the main reasons for the implementation of character education for all levels of education, from primary to tertiary education. Character education is a learning process by familiarizing children to think and behave and helping individuals to live and work together as families, communities and nations, as well as helping others to make responsible decisions. Conceptually, the character education models include: monolithic models, integrated models in all fields of study, models outside of teaching and combined models. Meanwhile, the implementation of character education can be done through self-development programs, integrated in subjects and extracurricular activities or school culture.